2008
DOI: 10.1016/j.ijpharm.2007.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Improved oral bioavailability and brain transport of Saquinavir upon administration in novel nanoemulsion formulations

Abstract: The aim of this investigation was to develop novel oil-in-water (o/w) nanoemulsions containing saquinavir (SQV), an anti-HIV protease inhibitor, for enhanced oral bioavailability and brain disposition. SQV was dissolved in different types of edible oils rich in essential polyunsaturated fatty acids (PUFA) to constitute the internal oil phase of the nanoemulsions. The external phase consisted of surfactants Lipoid ® -80 and deoxycholic acid dissolved in water. The nanoemulsions with an average oil droplet size … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
97
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(103 citation statements)
references
References 25 publications
(24 reference statements)
2
97
0
Order By: Relevance
“…[24][25][26][27] It has been also reported that intranasal administration of micro/nanoemulsions could have a brain-targeting effect. [28][29][30][31][32][33][34][35][36][37] In the present study, we confirmed that a CLA-PTX microemulsion administered intravenously could also produce antitumor activity in brain tissue.…”
Section: Discussionsupporting
confidence: 84%
“…[24][25][26][27] It has been also reported that intranasal administration of micro/nanoemulsions could have a brain-targeting effect. [28][29][30][31][32][33][34][35][36][37] In the present study, we confirmed that a CLA-PTX microemulsion administered intravenously could also produce antitumor activity in brain tissue.…”
Section: Discussionsupporting
confidence: 84%
“…46,47 Several lipid based formulations such as saquinavir (Fortovase®, Roche Pharmaceuticals, NJ, USA), ritonavir (Norvir®, Abbott Laboratories, IL, USA), cyclosporin (Neoral®, Novartis Pharmaceutical Ltd., Surrey, UK) were approved by regulatory agencies and given impetus for development of lipid based formulations for the improved oral delivery of poorly water soluble drugs. Nanoemulsion drug delivery have been reported to improve the bioavailability of hydrophobic drugs very effectively 53,54 , increased in vivo performance of anticancer drugs, e.g., dacarbazine 55 and camptothecin. 56 In our present study, we have formulated RST and KT nanoemulsions as a carrier for new DDX3 helicase inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…Mucoadhesive MEs could further enhance nose to brain targeting through improved residence time (Vyas et 2006a, 2006bJogani et al, 2008). The high brain delivery of saquinavir, an anti-HIV drug following oral administration of an ME containing flaxseed oil was attributed to docosahexaenoic acid (DHA)-mediated bypass of the BBB (Vyas et al, 2008). Moreover, DHA as a brain nutrient could provide additional advantage.…”
Section: Introductionmentioning
confidence: 99%